Enhancing food supply chain resilience through the utilisation of digital and sequence information technologies - Anbumozhi, Venkatachalam; Babu, Suresh Chandra; Bollino, Carlos Andrea; Craig, Wendy; Kulandivelu, Ponmalai; Moronta-Barrios, Felix; Yamaji, Eji (T20 Italy, 2021)
Digitally enabled food value chains and plant breeding programmes can improve resilience to agricultural productivity fluctuations and food insecurity. Digital innovations and economic values unlocked by online genetic data or digital sequence information (DSI) and other digital technologies must maximise positive social and environmental impacts and avoid exasperating global supply chain risks. This brief addresses three areas where immediate actions are needed by the G20: first, coordination that facilitates the adoption of digital transformations in food value chains; second, the creation of DSI-enabling institutional environments; third, steering basic research funding to encourage multi-disciplinary research that bridges technology, social, and environmental disciplines.